Analysis of rational use and misuse of antibiotics in emergency departments: A cross-sectional study - Huseyin Gurbuz; Selda Aslan; Muhammet Emin Doğan; Mehmet Ali Çevik (PLoS ONE, 2026)
Objective To assess antibiotic prescribing frequency and the appropriateness of prescriptions based on established rational antibiotic use principles among adult patients evaluated in the emergency department. Methods This retrospective, cross-sectional study was conducted in the emergency department of a tertiary university hospital between 1 January and 30 June 2022. Adult patients (≥18 years) who received or were prescribed antibiotics were included. Demographic, clinical, and microbiological data were retrieved from the hospital information management system. Prescriptions were evaluated against rational antibiotic use criteria defined by the World Health Organization (WHO) and the Turkish Medicines and Medical Devices Agency (TİTCK). Results A total of 595 patients were analyzed (62.4% female; mean age, 31.1 ± 14.2 years). Antibiotics were prescribed in 95.8% of encounters. Amoxicillin–clavulanic acid was the most commonly used agent (58.7%), followed by amoxicillin (8.7%) and metronidazole (5.6%). Microbiological culture sampling was conducted in only 0.8% of cases. Among patients who received antibiotic therapy (n = 570), 87.2% of prescriptions were classified as appropriate and 12.8% were classified as inappropriate according to guideline-based evaluation. In the overall cohort, 4.2% of patients did not receive antibiotic therapy. Most treated patients received a single antibiotic (95.8%), whereas dual antibiotic therapy was infrequently used (4.0%). Conclusion Antibiotic prescribing in the emergency department was notably high, accompanied by critically low rates of microbiological investigation. The findings demonstrate a persistent reliance on empirical therapy. Enhancing diagnostic support, promoting culture-guided treatment, and incorporating routine antimicrobial de-escalation strategies may help strengthen rational antibiotic use and warrant further evaluation.